Kidney glycosphingolipids are elevated early in diabetic nephropathy and mediate hypertrophy of mesangial cells - Subathra, Marimuthu; Korrapati, Midhun; Howell, Lauren A.; Arthur, John M.; Shayman, James A.; Schnellmann, Rick G.; Siskind, Leah J. (American journal of physiology. Renal physiology, 2015)
Glycosphingolipids (GSLs) play a role in insulin resistance and diabetes, but their role in diabetic nephropathy (DN) has received limited attention. We used 9- and 17-wk-old nondiabetic db/ m and diabetic db/ db mice to examine the role of GSLs in DN. Cerebrosides or monoglycosylated GSLs [hexosylceramides (HexCers); glucosyl- and galactosylceramides] and lactosylceramide (LacCers) were elevated in db/ db mouse kidney cortices, specifically in glomeruli, and also in urine. In our recent paper (25), we observed that the kidneys exhibited glomerular hypertrophy and proximal tubular vacuolization and increased fibrosis markers at these time points. Mesangial cells contribute to hyperglycemia-induced glomerular hypertrophy in DN. Hyperglycemic culture conditions, similar to that present in diabetes, were sufficient to elevate mesangial cell HexCers and increase markers of fibrosis, extracellular matrix proteins, and cellular hypertrophy. Inhibition of glucosylceramide synthase or lowering glucose levels decreased markers of fibrosis and extracellular matrix proteins and reversed mesangial cell hypertrophy. Hyperglycemia increased phosphorylated (p)SMAD3 and pAkt levels and reduced phosphatase and tensin homolog levels, which were reversed with glucosylceramide synthase inhibition. These data suggest that inhibition of glucosylceramide synthase reversed mesangial cell hypertrophy through decreased pAkt and pSmad3 and increased pathways responsible for protein degradation. Importantly, urinary GSL levels were higher in patients with DN compared with healthy control subjects, implicating a role for these lipids in human DN. Thus, hyperglycemia in type II diabetes leads to renal dysfunction at least in part by inducing accumulation of HexCers and LacCers in mesangial cells, resulting in fibrosis, extracellular matrix production, and hypertrophy.